2022
DOI: 10.1002/aenm.202103663
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Electrocatalytic CO2 Reduction to C2+ Products by Adjusting the Local Reaction Environment with Polymer Binders

Abstract: sequestrated. Recently, electrochemical CO 2 reduction reactions (CO 2 RR) enabled by renewable energy have been suggested as a promising strategy to solve these problems, sequestrating discharged CO 2 into chemical feedstocks, and downscaling the use of fossil fuels in the chemical production industry. In addition, CO 2 RR is an efficient way to store electricity generated from intermittent renewable energies in the form of liquid fuels for transport and other applications. [3][4][5] Copper-based materials ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
89
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 106 publications
(113 citation statements)
references
References 49 publications
(50 reference statements)
4
89
0
Order By: Relevance
“…Much has been adopted from the already matured electrochemical hydrogen evolution reaction (HER) field, where performance metrics such as >1 A cm –2 conversion and >10,000 h lifetime are easily surpassed . By adopting technical features like the gas diffusion electrode (GDE) and membrane electrode assembly (MEA) cell architecture, the field of CO 2 reduction has achieved industrially relevant current densities (>200 mA cm –2 ) while retaining selective conversion. These improvements were in part realized by utilizing highly alkaline electrolytes, such as KOH, to limit the competing HER , and humidifying the CO 2 gas stream to manage water availability to the cathode and membrane. , However, since being incorporated into more industrial reactors, additional challenges have been found which impact the long-term stability and economic feasibility of CO 2 RR.…”
mentioning
confidence: 99%
“…Much has been adopted from the already matured electrochemical hydrogen evolution reaction (HER) field, where performance metrics such as >1 A cm –2 conversion and >10,000 h lifetime are easily surpassed . By adopting technical features like the gas diffusion electrode (GDE) and membrane electrode assembly (MEA) cell architecture, the field of CO 2 reduction has achieved industrially relevant current densities (>200 mA cm –2 ) while retaining selective conversion. These improvements were in part realized by utilizing highly alkaline electrolytes, such as KOH, to limit the competing HER , and humidifying the CO 2 gas stream to manage water availability to the cathode and membrane. , However, since being incorporated into more industrial reactors, additional challenges have been found which impact the long-term stability and economic feasibility of CO 2 RR.…”
mentioning
confidence: 99%
“…In addition to the carbon support, the employed binder also plays a key role in tailoring the local environment around the catalytic particles. 37 Therefore, we altered the employed fluoropolymer binder from PTFE to PVDF as well as the added amount, to identify further tuning points. Overall, both PVDF and PTFE bound electrodes on SGL-GFD show FE values for the ECH of over 50%, with PTFE electrodes outcompeting their polymeric counterparts both in terms of activity for the ECH and specifically for the generation of MBE (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Similarly, Luo et al employed fluorinated ethylene propylene (FEP) as a binder for the Cu catalyst to inhibit the competing HER reaction in aqueous CO 2 RR. 15 Nafion (with both hydrophilic and hydrophobic functional groups) and PAA (with hydrophilic functional groups) were also selected as binders to adjust the local environment of the Cu catalyst. The catalyst was prepared by dispersing both as-synthesized CuO particles and polymer in isopropyl alcohol and subsequent drop-casting on the electrode.…”
Section: Tailoring the Local Environment Of Copper Nanocatalysts For ...mentioning
confidence: 99%
“…Electrolyte (light blue), Cu (brownish red), polymer binder (gray), CO 2 pathway (red arrow), H + pathway (blue arrow), and trapped CO 2 in hydrophobic samples (white). Reproduced with permission from ref ( 15 ). Copyright 2022 Wiley-VCH.…”
Section: Tailoring the Local Environment Of Copper Nanocatalysts For ...mentioning
confidence: 99%